A new freshwater goby of Rhinogobius Gill, 1859 (Teleostei, Gobiidae) from the Jangshi basin, Fujian Province, southeastern China - Chen, I-Shiung; Chen, Kwang-Yiao; Wang, Shen-Chih (Zootaxa, 2024)
A new species of freshwater gobiid fish of genus Rhnogobius Gill, 1859, were collected from the Jangshi river basin, southern region of Fujian Province, China. Rhinogobius jangshiensis new species can be well distinguished from other congeners by their specific patterns of coloration and meristic features: (1) fins rays: second dorsal fin rays I/8; anal fin rays I/7; pectoral fin rays modally 17; (2) squamation: longitudinal scale series 28–30 (modally 29); perdorsal scales 9–10 (modally 9); vertebral count 27; and (3) specific colouration pattern: cheek with 4 main oblique black stripes in male; branchiostegal membrane grayish blue with about 26–32 rounded, brilliant orange red spots in male; caudal fin gray with some light rounded spots and basal black spotted patch and large central yellow mark in adult male. A diagnostic key to all valid species from Fujian Province, China would be provided in this paper.